Subterranean rodents of the genus Ctenomys (Caviomorpha, Ctenomyidae) follow the converse to Bergmann's rule - Medina, Alonso Ismael (2007)
Aim: We analysed body-size variation in relation to latitude, longitude, elevation and environmental variables in Ctenomys (tuco-tucos), subterranean rodents in the Ctenomyidae (Caviomorpha). We tested the existence of inter- and intraspecific size clines to determine if these rodents follow Bergmann's rule, to compare intra- and interspecific size trends and to assess the relevance of the subterranean lifestyle on these trends. Location: South America, south of 15° latitude. Methods: This paper is based on 719 specimens of tuco-tucos from 133 localities of Argentina, Bolivia, Chile, Paraguay, Peru and Uruguay, representing 47 named species and 32 undescribed forms. Intraspecific analyses were performed for Ctenomys talarum Thomas, 1898 and the Ctenomys perrensi Thomas, 1896 species complex. Head and body length and weight were used for estimating body size. Geographical independent variables included latitude, longitude and altitude. Environmental independent variables were mean minimal and maximal monthly temperature, mean annual temperature, mean minimal and maximal precipitation, and total annual precipitation. To estimate seasonality, the annual variability of the climatic factors was calculated as their coefficients of variation and the difference between maximum and minimum values. Mean annual actual evapotranspiration (AET), and mean annual, January (summer) and July (winter) potential evapotranspiration (PET) values were also calculated for each locality, as well as annual, summer and winter water balance (WB). Statistical analyses consisted of simple and multiple regression and nonparametric correlation. Results: Body size of Ctenomys decreases interspecifically from 15°00′ S to 48°15′ S and from 56°33′ W to 71°46′ W, and is positively correlated with ambient temperature and precipitation. The best predictors of body size according to multiple regression analyses were mean annual temperature, the difference between mean maximum and minimum annual temperatures, annual PET, the difference between summer and winter PET, and annual and winter water balance. These patterns are repeated, but not identically, at a smaller geographical scale within the species C. talarum and the superspecies C. perrensi. Main conclusions: Tuco-tucos follow the converse to Bergmann's rule at the interspecific level. At the intraspecific level some parallel trends were observed, but the smaller scale of these analyses, involving a very reduced variation of environmental factors, necessitates caution in interpreting results. The subterranean lifestyle probably insulates these rodents from the external temperature. The observed latitudinal body-size gradients are more probably related to seasonality, ambient energy, primary productivity and/or intensity of predation. © 2007 The Authors.